Optimalisasi Media Digital YouTube dalam Pembelajaran Pendidikan Agama Islam: Strategi Guru dalam Meningkatkan Motivasi Belajar dan Akhlak Siswa di MTsN 7 Madiun - Milu Atsna Mufida (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2025)
Digital transformation has changed the learning paradigm at various levels of education, including in Islamic Religious Education (PAI). The use of digital media, particularly YouTube, offers opportunities to increase learning motivation while also serving as a means of internalizing moral values ​​to students. This study aims to analyze the strategies of Islamic Religious Education teachers in improving student learning motivation and moral values ​​through YouTube digital media at MTsN 7 Madiun. The study used a qualitative approach with an interpretive phenomenology type. Data were obtained through observation, in-depth interviews, and documentation of Islamic Religious Education teachers, students, and learning documents. Data analysis was carried out through data reduction, data presentation, and drawing conclusions with validity tests using source and technique triangulation. The results of the study indicate that Islamic Religious Education teachers implement learning strategies through the use of Islamic learning videos, digital-based assignments, educational communication, and the integration of YouTube content with moral values ​​in the learning process. Moral development is carried out through teacher role models, habituation of Islamic behavior, supervision of students' digital activities, and reflection on the material learned. Supporting factors for implementing this strategy include the availability of digital madrasah facilities, parental support, teacher competence, and high student interest in digital media. Inhibiting factors include limited digital literacy among some students, the negative influence of social media, and suboptimal supervision of technology use outside the school environment. This study concludes that YouTube can be an effective learning medium if integrated with appropriate pedagogical strategies oriented toward Islamic character development.